(untitled) (Lakar: Jurnal Arsitektur, 2026)
Coastal tourism areas require spatial planning that responds to site characteristics while maintaining spatial quality and visual orientation. Previous studies on coastal tourism development mainly focus on tourism management and environmental planning, while architectural studies examining building mass configuration as a spatial framework of coastal tourism areas remain limited. This study aims to analyze the configuration patterns of building mass in coastal tourism areas based on site characteristics and to formulate a conceptual typology of mass arrangement. The research employs a qualitative comparative approach through spatial analysis of three coastal tourism areas: Heha Ocean View, Obelix Sea View, and Marina Beach. The analysis focuses on four spatial variables: building mass configuration, zoning system, circulation structure, and open space integration. The findings indicate that site topography significantly influences mass configuration patterns. Coastal areas with steep contours tend to develop clustered and terraced mass configurations, while flat coastal sites develop linear configurations parallel to the shoreline. Based on these findings, this study proposes a typological model of coastal tourism mass configuration consisting of clustered-terraced configuration and linear shoreline configuration. This study contributes to architectural theory by proposing a typological model of coastal tourism mass configuration based on site morphology.